PENINGKATAN PRESTASI BELAJAR PPKn MELALUI METODE NUMBERED HEADS TOGETHER PADA SISWA KELAS VII D SMPN 1 DURENAN - HERUCOKRO SURYA (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2023)
In the last 2 years, the learning achievement of VII D students in PPKn learning still shows very low learning outcomes. Many students often do not complete their Civics learning. The reason is that Civics is often boring because the material is difficult to understand and teachers still often use conventional learning methods and models. One of the efforts to improve the learning achievement of class VII D students, the researcher tried to use the Numbered Heads Together learning method in the learning that the researcher carried out. The aim of carrying out this classroom action research is to determine the increase in PPKn learning achievement regarding ethnic, religious, racial and inter-group diversity within the framework of Bhinneka Tunggal Ika through the numbered heads together method for class VII D students in semester 2 of the 2021/2022 academic year at SMPN 1 Durenan . The subjects in this classroom action research were class VII D students of SMP Negeri 1 Durenan. This research design consists of planning, action, observation and reflection stages. From the results of the implementation of PPKn learning from pre-cycle to the implementation of cycle I and cycle II research, it can be concluded that the application of the numbered heads together method can improve the PPKn learning achievement of class VII D students at SMP Negeri 1 Durenan Semester 2 2021/2022 in PPKn subjects. This can be seen from the increase in the percentage of students' learning completeness, namely in the first cycle it was 76.67% and in the second cycle it increased again until it reached 100% (all students completed). ABSTRAKDalam kurun waktu 2 tahun terakhir, prestasi belajar siswa VII D dalam pembelajaran PPKn masih menunjukkan hasil belajar yang sangat rendah. Banyak siswa yang sering tidak tuntas pada pembelajaran PPKn ini. Penyebabnya PPKn seringkali membosankan karena materinya sulit dipahami dan guru masih sering menggunakan metode dan model pembelajaran yang konvensional. Salah satu usaha untuk meningkatkan prestasi belajar siswa kelas VII D ini, peneliti mencoba menggunakan metode belajar Numbered Heads Together pada pembelajaran yang peneliti lakukan. Tujuan dari pelaksanaan penelitian tindakan kelas ini adalah untuk mengetahui peningkatan prestasi belajar PPKn materi keberagaman suku, agama, ras dan antar golongan dalam bingkai Bhinneka Tunggal Ika melalui metode numbered heads together pada siswa kelas VII D semester 2 tahun pelajaran 2021/2022 di SMPN 1 Durenan. Subyek dalam penelitian tindakan kelas ini adalah siswa kelas VII D SMP Negeri 1 Durenan. Rancangan penelitian ini terdiri dari tahapan perencanaan, tindakan, observasi dan refleksi. Dari hasil pelaksanaan pembelajaran PPKn mulai dari pra siklus hingga pelaksanaan penelitian siklus I dan siklus II dapat disimpulkan bahwa penerapan metode numbered heads together dapat meningkatkan prestasi belajar PPKn siswa kelas VII D SMP Negeri 1 Durenan Semester 2 Tahun 2021/2022 pada mata pelajaran PPKn. Hal ini dapat diketahui dari adanya peningkatan persentase ketuntasan belajar siswa, yaitu pada siklus I 76,67% dan pada siklus II meningkat lagi hingga mencapai 100% (seluruh siswa tuntas).